ANALISIS PENGARUH RETURN ON ASSET, DIVIDEND PAYOUT RATIO, ASSET GROWTH, DEBT TO EQUITY RATIO, DAN OPERATING LEVERAGE TERHADAP RISIKO SISTEMATIS (Studi Kasus pada Sektor Manufaktur yang Terdaftar di BEI Periode 2010-2014) - Purbawisesa, Annisa; Sampurno, R. Djoko (Diponegoro Journal of Management, 2016)
Investment in a stock market may be the most effective way to resolve the economic crisis since the stock market is a dependable source of income. Investors will get a considerable return if make a proper investment decisions and vice versa, so then it is needed both fundamental analysis and technical analysis. A good investment should consider the factors that influence the risk in order to obtain the expected return, the risk is systematic risk and unsystematic risk. Unsystematic risk is the risk that can be eliminated with a diversification in a stock portfolio, while systematic risk is the risk that can’t be eliminated by diversification. This study aimed to analyze the factors that can affect systematic risk, this factors include ROA, dividend payout ratio, asset growth, DER, and DOL.This study used a purposive sampling method, which selecting sample based on the criteria of research needs. The population of this study is 112 company of manufatured sectors that listed in BEI in the period 2010-2014, and there is a 25 companies that fulfilled the criteria, but because of the outliers, this study only used 18 companies as samples. The analysis method used in this research is a multiple regression analysis.The results of this study indicate that ROA, dividend payout ratio, asset growth, DER and DOL affect systematic risk simultaneously, while partially, only dividend payout ratio are negatively and significantly affect systematic risk.